Atmospheric Pressure Plasma Vapor Treatment of Thermo-sensitive Poly(N-isopropylacrylamide) and Its Application to Textile Materials (Journal of Fiber Bioengineering and Informatics, 2018)
Poly(N-isopropylacrylamide) (PNIPAAm) is a new type of smart thermo-sensitive macromoleculematerial that is characterized by a sudden precipitation on heating, switching from a hydrophilic toa hydrophobic state. In this paper, using the self-made equipment of atmospheric pressure plasma vaportreatment running in the environment of argon, PNIPAAm was deposited separately to PolybutyleneTerephthalate (PBT) melt-blown nonwovens and Polyester (PET) fabrics. It was found that thewettability and water permeability were significantly modified by changing the temperature above andbelow the Lower Critical Solution Temperature (LCST), according to the data derived from measurementsof water contact angle, water permeability time and Scanning Electron Microscopy (SEM) images.Considering human body temperature is close to the LCST, these results are valuable for furtherapplication to thermo-sensitive textile materials.
Keywords: Atmospheric Pressure Plasma; Plasma Treatment; Poly(N-isopropylacrylamide) (PNIPAAm); Lower Critical Solution Temperature (LCST); Water Contact Angle; Water Permeability Time